2020
DOI: 10.3892/ijmm.2020.4670
|View full text |Cite
|
Sign up to set email alerts
|

miR‑144‑3p inhibits the proliferation, migration and angiogenesis of multiple myeloma cells by targeting myocyte enhancer factor 2A

Abstract: Multiple myelomas (MM) are the second most common haematological malignancy, for which no curative treatments have been reported to date. MicroRNAs (miRNAs or miRs) have recently been shown to be involved in the proliferation of MM cells. However, the molecular mechanisms through which miRNAs regulate migration and angiogenesis in MM are poorly understood. Accordingly, the present study evaluated the role of miR-144-3p in MM. miR-144-3p exhibited a lower expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is known to have effects on a variety of diseases and to regulate the production of proteins by interacting with mRNA 16 , 33 , 34 . Previous studies have shown that miR-144-3p can regulate the proliferation, migration, invasion and biological behaviors of various tumor cells that are drug resistant 35 - 37 . For example, miR-144-3p promotes the tumor growth and metastasis of papillary thyroid carcinoma by targeting paired box gene 8 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have effects on a variety of diseases and to regulate the production of proteins by interacting with mRNA 16 , 33 , 34 . Previous studies have shown that miR-144-3p can regulate the proliferation, migration, invasion and biological behaviors of various tumor cells that are drug resistant 35 - 37 . For example, miR-144-3p promotes the tumor growth and metastasis of papillary thyroid carcinoma by targeting paired box gene 8 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNAs are related to multiple myeloma. miR-144, downregulated in MM patients and MM cell lines, targets MEF2a (myocyte enhancer factor 2A) and inhibits the proliferation, migration and angiogenesis of MM cells and the overexpression reverses the effects [ 132 ]. The direct target of miR-144 is transmembrane tyrosine kinase c-MET, which is involved in invasion, migration, proliferation and angiogenesis [ 133 ].…”
Section: Mirnas Involvement In Regulating Periphery B-cellsmentioning
confidence: 99%
“…Transforming growth factor (TGF)-β plays a role in the invasion, metastasis and growth of cancer cells by promoting HDAC degradation and histone hyper-acetylation at the MEF2 site of the matrix metalloproteinase (MMP-10) promoter, and by activating MEF2A and up-regulating the expression of MMP-10 [103]. MEF2A expression is thought to promote the progression of multiple myeloma [104] and of colorectal cancer [105], with higher expression correlating with poor prognosis. P38 MAPK activation in the gastric cancer cell line MKN45 up-regulates GLUT-4 in a MEF2Adependent manner and promotes glucose uptake and cell growth [106].…”
Section: The Role Of Mef2a In Tumorsmentioning
confidence: 99%
“…MiR-155 for example inhibits the expression of MEF2A, while the lncRNA malat1 up-regulates the expression of MEF2A by adsorbing miR-155, thus promoting cardiomyocyte proliferation [135]. miR-144-3P was shown to have antitumor properties by inhibiting the expression of MEF2A [104], while miR-194-5p delays the progression of sepsis by down-regulating MEF2A [136].…”
Section: Regulation Of Mef2a Expressionmentioning
confidence: 99%